ANALYSIS OF NEEDS FOR THE NUMBER OF EMPLOYEES BASED ON WORKLOAD CALCULATIONS IN THE COMPANY MEDAN CITY MARKET AREA - Dicky Habibie; Nazaruddin; Yeni Absah (RADJA PUBLIKA, 2023)
The aim of this research is to determine and analyze the number of employees and workload available in work units (sections, sections or departments) at PD Pasar Kota Medan. This research is quantitative research. According to (Arikunto 2019:27) quantitative research is a research method that, as the name suggests, requires a lot of use of numbers, starting from data collection, interpretation of the data, and the appearance of the results. The sampling technique in this research is the Simple Random Sampling Method. Simple Random Sampling